Autophagy in Staphylococcus aureus Infection - Wang, Mengyao; Fan, Ziyao; Han, Hongbing (Frontiers in Cellular and Infection Microbiology, 2021)
Staphylococcus aureus is an invasive, facultative intracellular pathogen that can colonize niches in various host organisms, making it difficult for the host immune system to completely eliminate. Host cell autophagy is an intracellular clearance pathway involved in degrading S. aureus. The mechanism by which the S. aureus accessory gene regulatory system resists and even utilizes autophagy to escape the host immune system has been gradually understood. This article reviews the interaction between autophagy and S. aureus, providing insights on how to use these mechanisms to improve S. aureus infection control.